2022
DOI: 10.3389/fonc.2022.943326
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomics analysis reveals the associations of dynamic contrast-enhanced–MRI features with gene expression characteristics, PAM50 subtypes, and prognosis of breast cancer

Abstract: BackgroundTo investigate reliable associations between dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) features and gene expression characteristics in breast cancer (BC) and to develop and validate classifiers for predicting PAM50 subtypes and prognosis from DCE-MRI non-invasively.MethodsTwo radiogenomics cohorts with paired DCE-MRI and RNA-sequencing (RNA-seq) data were collected from local and public databases and divided into discovery (n = 174) and validation cohorts (n = 72). Six external d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…Su et al developed a radiomics model for tumor-infiltrating lymphocyte status based on GLCM and GLSZM texture features [ 40 ]. Ming et al also revealed that cell cycle pathway exhibited significant associations with SurfaceVolumeRatio (PRF9 and PRF10 in our study) [ 75 , 76 ]. Hence, these results demonstrated the credibility of links between immuno-oncological characteristics and imaging features.…”
Section: Discussionsupporting
confidence: 75%
“…Su et al developed a radiomics model for tumor-infiltrating lymphocyte status based on GLCM and GLSZM texture features [ 40 ]. Ming et al also revealed that cell cycle pathway exhibited significant associations with SurfaceVolumeRatio (PRF9 and PRF10 in our study) [ 75 , 76 ]. Hence, these results demonstrated the credibility of links between immuno-oncological characteristics and imaging features.…”
Section: Discussionsupporting
confidence: 75%
“…In the clinic, various imaging techniques are applied to diagnose BC, such as ultrasound, mammography, and MRI; among these, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) data are widely used in BC radiomics or radiogenomics studies for their advantages in high quality and three-dimension resolution. However, most studies focus on uncovering the relationship between medical imaging features and the molecular or clinical characteristics of the disease, and few have analyzed the disease heterogeneity in imaging phenotypes from an independent perspective [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between image phenotypes and biological pathways has been shown in numerous studies, suggesting the possibility of observing cancer-related pathways in a non-invasive manner by DCE-MRI. For example, prognostic radiomic phenotypes of glioblastoma cells could be classified into four types based on the potential pathways of radiomic phenotypes, reflecting key biological processes related to immune regulation, tumor proliferation, therapeutic response and cellular functions, all of which affect patient survival outcomes [ 30 ]; genes in the cell cycle pathway exhibited significant associations with MRI imaging phenotypes [ 31 ]. The inhomogeneous enhancement phenotypes of tumor-adjacent parenchyma in MR imaging were associated with tumor necrosis signaling pathways [ 32 ].…”
Section: Discussionmentioning
confidence: 99%